Perlindungan Hukum Pemegang Hak Cipta terhadap Pelanggaran Melalui Aplikasi Telegram - Martha Elizabeth Sutrahitu; Sarah Selfina Kuahaty; Agustina Balik (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The distribution of cinematographic works is so much at this time, especially in the channel on the Telegram application.Purposes of the Research: Know the form of legal protection of cinematographic copyright holders whose rights are violated on the telegram application, as well as the legal consequences for the parties who commit the violation.Methods of the Research: The research method used is juridical normative, the problem approach used in the research is the statutory approach and the conceptual approach. Sources of legal materials used are primary, secondary and tertiary legal materials. The technique of collecting legal materials used in this study is a research library, then analyzed using qualitative methods.Results of the Research: Based on research, currently the distribution of cinematographic works without a creator or copyright holder is a violation that results in losses for both creators and copyright holders, but to prevent such violations there are protections provided to protect cinematographic works, including: preventive legal protection with limitations in several laws such as UUHC and UU ITE as well as providing Joint Regulations MENKUMHAM and MENKOMINFO regarding the Implementation of Closure of Content and/or Related Rights in Electronic Systems, repressive legal protection in the form of non-litigation efforts that focus on efforts to settle out of court (Alternative disputes and arbitration institutions), as well as litigation efforts carried out through the courts. Commercial Court and report closure of content and/or access rights). The legal consequences that are accepted for those who feel aggrieved, because the application is a loss and the legal consequences for those who violate the cinematographic works are subject to sanctions.